Students’ entrepreneurial behavior in the application of 'EkRenFaTiHa' productive entrepreneurial teaching model at culinary programs vocational schools - Badraningsih Lastariwati; Pardjono Pardjono; Sukamto Sukamto (REID (Research and Evaluation in Education), 2016)
The purpose of the study is to observe students' entrepreneurial behaviors in the implementation of entrepreneurship processes in production subjects. The study applied production entrepreneurial teaching model to some vocational high school students with their ‘EkRenFaTiHa Catering’ as their project. The entrepreneur process was integrated in the catering production subject and it consisted of the following aspects: Exploration, business plans, facilitation, action and output. The study employed research and development approach, which referred to Plomp development model. The data were analyzed by using descriptive statistics. The research subjects were some students of 1 Sewon State Vocational High School. The results of the test on the model implementation show the students’ mastery of the entrepreneurial behaviors showing the characteristics of responsibility, innovation, honesty, independence, creativity, leadership, dilligence, discipline, cooperation, risk-taking and good communication. It also shows that there is a concrete improvement during the continuous process regarding every observed entrepreneurial behavior, and in general the students’ entrepreneurial behaviors could be classified as good.